Distinct spectra of somatic mutations accumulated with age in mouse heart and small intestine - Dollé, Martijn E. T. (The National Academy of Sciences, 2000)
Somatic mutation accumulation has been implicated as a major cause of cancer and aging. By using a transgenic mouse model with a chromosomally integrated lacZ reporter gene, mutational spectra were characterized at young and old age in two organs greatly differing in proliferative activity, i.e., the heart and small intestine. At young age the spectra were nearly identical, mainly consisting of G·C to A·T transitions and 1-bp deletions. At old age, however, distinct patterns of mutations had developed. In small intestine, only point mutations were found to accumulate, including G·C to T·A, G·C to C·G, and A·T to C·G transversions and G·C to A·T transitions. In contrast, in heart about half of the accumulated mutations appeared to be large genome rearrangements, involving up to 34 centimorgans of chromosomal DNA. Virtually all other mutations accumulating in the heart appeared to be G·C to A·T transitions at CpG sites. These results suggest that distinct mechanisms lead to organ-specific genome deterioration and dysfunction at old age.